RNA Quantitative Analysis from Fixed and Paraffin-Embedded Tissues: Membrane Hybridization and Capillary Electrophoresis - Giorgio Stanta; Serena Bonin (BioTechniques)
Fixed and paraffin-embedded tissues from pathology department archives are available for RNA expression analysis. We describe a general method for quantitation of specific RNA sequence extracted from single 6–8-μm human histological tissue sections cut from paraffin blocks. For each specific mRNA, the range of linear relationship between the log of the initial total RNA concentration and the log of the specific product after reverse transcription (RT)-PCR must be established. We usually perform RT with avian myeloblastosis virus (AMV)-RT, using specific antisense primers and a variable number of cycles of PCR amplification. The number of cycles must be adjusted within the range in which a linear relationship exists between the log of the amount of amplification product and the number of cycles. The quantity of specific product is standardized relative to β-actin mRNA to normalize for the degree of RNA degradation, which can be quite different among samples. The amplification products were quantified by dot blot and 32P-labeled hybridization probe or by capillary electrophoresis with a laser-induced fluorescence detector. The intratest variation range was for the dot blot mean ±10% standard deviation (SD) and for the capillary electrophoresis mean ±3% SD.